PENGUATAN KESADARAN TERKAIT PENTINGNYA PEMERIKSAAN KEHAMILAN (ANTENATAL CARE/ANC) DI DESA MEKAR SARI TAHUN 2024 - Krisna, Putri; Ariescha, Putri Ayu Yessy; Sari, Nurmala; Hutabarat, Vitrilina; Hadi, Milvan; Halawa, Kris Angelina (Jurnal Pengabdian Masyarakat Putri Hijau, 2024)
Maternal Mortality Rate (MMR) is an important indicator to assess maternal health efforts and societal development. Indonesia ranks third in MMR within ASEAN countries. Antenatal care ensures maternal health and infant safety through prevention efforts such as education and interventions to address dangerous symptoms during pregnancy. Factors influencing antenatal care utilization include maternal age, education level, pregnancy planning, parity, birth spacing, knowledge, attitude, economic factors, availability, distance, health history, perception of health, and access to obstetric services. Improving accessibility, economic conditions, and media exposure can boost antenatal care utilization rates globally.